The effect of taxes on CEO performance - Laura Arnemann; Florian Buhlmann; Martin Ruf; Johannes Voget (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2025)
In this paper, we investigate the effect of higher personal income taxes on CEO and firm performance in publicly traded US firms. In response to higher taxes on compensation, CEOs are less likely to reach performance goals and spend more time working in boards outside of their firm. At the same time, firm performance drops before eventually recovering as investment projects with below average profitability are disregarded and due to adjustments in CEO compensation.
Keywords: H24; M12; 330; Executive Compensation; Personal Income Taxation; Firm Performance